The Effect of Length of A3-51 Probiotic Supplementation to The Number of Intestine Enterobacteriaceae in Oreochromis niloticus - Dewi Desnilasari; Sukanto Sukanto; Agus Irianto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2006)
The aim of this research was to know the effect of length of A3-51 probiotic supplementation to the number of intestine Enterobacteriaceae. Research used experimental method using Completely Randomized Design which was based on 4 treatments i.e. La (without probiotic), Ll (probiotic supplementation for 7 days), L2 (probiotic supplementation for 14 days), L3 (probiotic supplementation for 21 days). Each treatment was repeated 3 times. The result showed that the length period of A3-51 probiotic supplementation very significantly (P<0,01) increased the intestine Enterobacteriaceae number. However, in the same time the amount of pathogenic Enterobacteriaceae decreased. In addition, probiotic supplementation improved protein, fat, and carbohydrate digestions. Key words: Enterobacteriaceae, intestine, probiotic, nutrient digestibility